Клиническая оценка эффективности применения диодного лазера при эндодонтическом лечении хронических форм пульпитов (LLC "Endo Press", 2020)
In article data of the modern literature on complications of treatment of chronic illnesses of a pulp. Application of modern laser technologies in endodontic urged to help with treatment improvement of quality. The comparative estimation of efficiency application the diode laser is spent at endodontic treatment chronic forms pulpitis in the nearest and remote terms of supervision with traditional methods of treatment. Data of clinical, tool and radiological researches of 146 patients who were under supervision in a current of 24 months at which 184 teeth concerning a chronic pulpitis either removal of tooth pulp on orthopedic or parodontics indications has been cured are processed. Results of clinical researches have shown decrease in quantity of complications in group with application the diode laser for endodontic processing of root channels in the remote terms of supervision in 3,8 times in comparison with group of patients at which processing was spent traditional. Clinical examples are resulted.